2018
DOI: 10.1002/joc.5946
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall monitoring network design using conditioned Latin hypercube sampling and satellite precipitation estimates: An application in the ungauged Ecuadorian Amazon

Abstract: Rain gauge networks are crucial for enhancing the spatio-temporal characterization of precipitation. In tropical regions, scarcity of rain gauge data, climatic variability, and variable spatial accessibility make conventional approaches to design rain gauge networks inadequate and impractical. In this study, we propose the use of conditioned Latin hypercube sampling (cLHS) method with multi-temporal layers of remotely sensed precipitation measurements for capturing the spatio-temporal precipitation patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 100 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…cHLS is a sampling strategy in which x new sites are chosen such that the multivariate distribution is maximally stratified (Minasny & McBratney, 2006). While cLHS has mostly been used within digital soil mapping (e.g., Chu et al, 2010; Mulder et al, 2013; Silva et al, 2015; Stumpf et al, 2016), some studies have utilized cLHS for other environmental applications (e.g., Contreras et al, 2019; Lin et al, 2009; Villarreal et al, 2019; Yin et al, 2016, 2017). We applied the cLHS algorithm to identify 3000 sites around the globe (because SRDBv5 has >3000 data entries) in locations that maximize the representation of the multivariate space of the previously selected environmental covariates used to model Rs.…”
Section: Methodsmentioning
confidence: 99%
“…cHLS is a sampling strategy in which x new sites are chosen such that the multivariate distribution is maximally stratified (Minasny & McBratney, 2006). While cLHS has mostly been used within digital soil mapping (e.g., Chu et al, 2010; Mulder et al, 2013; Silva et al, 2015; Stumpf et al, 2016), some studies have utilized cLHS for other environmental applications (e.g., Contreras et al, 2019; Lin et al, 2009; Villarreal et al, 2019; Yin et al, 2016, 2017). We applied the cLHS algorithm to identify 3000 sites around the globe (because SRDBv5 has >3000 data entries) in locations that maximize the representation of the multivariate space of the previously selected environmental covariates used to model Rs.…”
Section: Methodsmentioning
confidence: 99%
“…In our case studies, SRS and cLHS were equivalent in terms of map accuracy. Several studies (e.g., Castro‐Franco, Costa, Peralta, & Aparicio, 2015; Chu, Lin, Jang, & Chang, 2010; Contreras, Ballari, De Bruin, & Samaniego, 2019; Domenech, Castro‐Franco, Costa, & Amiotti, 2017; Schmidt et al, 2014) concluded that cLHS in combination with kriging or random forest for mapping gave the most accurate prediction. These studies promote the use of cLHS as an effective sampling design for mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic monitoring of flood events is necessary for the validation of flood risk and hazard models that will help in the decision-making process. Since a high spatial and temporal variability of rainfall is expected within the Andean mountain range, efficient distribution of new types of hydrometeorological networks is required [e.g., Contreras et al (2019)] to reduce investment and maintenance costs, but without compromising modeling accuracy (Sucozhañay and Célleri, 2018). In recent years, citizen science has shown an increasing potential for hydrological data collection in remotes areas such as mountains by applying simple downloading procedures from What is required to assess, improve, and innovate flood recovery plans (e.g., "build back better" practices)?…”
Section: Improved Data Collectionmentioning
confidence: 99%